Comparative Physico-Chemical Properties of Fish Oil from Hyperopisus bebe, Marcusenius macrophthalmus and Mormyrus rume, Family Mormyridae - Suleiman, B. (Nigerian Journal of Animal Science, 2023)
A study was carried out to investigate the physico-chemical characteristics of fish oil. The experimental fish species studied were Hyperopisus bebe, Marcusenius macrophthalmus and Mormyrus rume belonging to the freshwater fish family Mormyridae. Extracted fish oil was evaluated for saponification, acid, iodine and peroxide values following standard procedures of the Association of Analytical Chemists. Mormyrus rume had the highest acidic and iodine values of 15.99 mg KOH/g and 13.01 gI2/100g, respectively, it therefore wields a greater comparative advantage compared to the 12.28 mg KOH/g, 11.74 gI2/100g and 15.99 mg KOH/g, 13.01 gI2/100g obtained for M. macrophthalmus and M. rume, respectively. The three fish species were generally high in fatty acids; therefore possess great oxidative storage stability as indicated by the low iodine values. The mormyrids’ oil is therefore considered safe for human consumption (peroxide value <5.0 meq/Kg). However, M. rume oil is recommended over the other two species within the family Mormyridae.